2009
DOI: 10.1890/08-0405.1
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of two sympatric rodents in a variable environment: rainfall, resource availability, and predation

Abstract: Precipitation plays an important role in the dynamics of species found in arid and semiarid environments. However, population fluctuations generally are driven by a combination of multiple factors whose relative contribution may vary through time and among species. We monitored fluctuations of species in three trophic levels for >17 years at a semiarid community in north-central Chile. The region is strongly affected by the El Niño Southern Oscillation, resulting in high variation in rainfall that triggers dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 65 publications
13
140
1
3
Order By: Relevance
“…nonlinear), suggesting that rainfall immediately enhances rat survival, but this effect rapidly becomes saturated. These results confirm previous studies conducted on tropical continental systems that showed a boost in rodent population dynamics, including individual survival [13], generated by an increase in primary productivity lagging behind rainfall pulses, as resource pulses move through trophic webs [45,46]. However, in the Galapagos correlations between rainfall pulses and rodent abundances were not systematic within the same Spatio-temporal modelling of rats J. C. Russell & L. Ruffino 771 island but depended mostly on habitat characteristics, such as vegetation cover or local climate [47].…”
Section: Discussionsupporting
confidence: 91%
“…nonlinear), suggesting that rainfall immediately enhances rat survival, but this effect rapidly becomes saturated. These results confirm previous studies conducted on tropical continental systems that showed a boost in rodent population dynamics, including individual survival [13], generated by an increase in primary productivity lagging behind rainfall pulses, as resource pulses move through trophic webs [45,46]. However, in the Galapagos correlations between rainfall pulses and rodent abundances were not systematic within the same Spatio-temporal modelling of rats J. C. Russell & L. Ruffino 771 island but depended mostly on habitat characteristics, such as vegetation cover or local climate [47].…”
Section: Discussionsupporting
confidence: 91%
“…By contrast to larger-bodied mammals, rodents, particularly smallsized species (i.e., <500 g), are often relatively robust to human disturbance and many species live commensally with humans (33,34). Due to their generally rapid reproductive rates and small home range sizes, populations can fluctuate dramatically over both small spatial and temporal scales, and in response to declines or removals of either rodent predators or rodent competitors, including large herbivores (35)(36)(37). Because both large predators and herbivores face a high risk of decline from human disturbances (6,10), susceptible host regulation may be a strong potential pathway by which wildlife loss can affect human disease risk.…”
Section: Significancementioning
confidence: 99%
“…25 Most rodent species responded directly to fluctuations in food availability, and population densities are driven by changes in food resources. 26,27 Vegetation also provides shelter and safety and keeps rodents from predators. Meanwhile, meteorological factors, especially temperature and precipitation, were also closely associated with the transmission of HFRS.…”
Section: Discussionmentioning
confidence: 99%